Lithium metal battery and electronic device

By coating the separator of the lithium metal battery with high graphitization, the problem of forming the lithium dendrites is solved, and the uniform deposition of lithium ions and the improvement of battery performance is achieved.

CN119890398APending Publication Date: 2025-04-25NINGDE AMPEREX TECHNOLOGY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510198662.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Lithium metal batteries are prone to form lithium dendrite structures during charging, resulting in uneven deposition of lithium ions, increasing the risk of short circuits, and aggravate the breakage and peeling of the SEI protective film on the negative electrode surface.

Method used

The electric field, ion field and temperature field are uniformized by coating a one-dimensional carbon material on the separator of the lithium metal battery, especially carbon nanofibers and carbon nanotubes with a graphitization degree of between 70% and 95%, thereby inhibiting the growth of lithium dendrites.

Benefits of technology

More uniform deposition of lithium ions is achieved, the generation and growth of lithium dendrites are reduced, the rupture of SEI film is reduced, the capacity retention rate of lithium metal batteries under large-scale cycles is improved, and the volume expansion is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890398A_ABST
    Figure CN119890398A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium metal battery and an electronic device. The lithium metal battery comprises a negative pole piece, a positive pole piece, a diaphragm and electrolyte, wherein the negative pole piece comprises a negative current collector and a lithium metal layer arranged on at least part of the surface of the negative current collector; the diaphragm comprises a base membrane and a composite coating arranged on one side, facing the negative electrode plate, of the surface of the base membrane, the composite coating comprises a one-dimensional carbon material, the graphitization degree of the one-dimensional carbon material is X%, and X is larger than or equal to 70 and smaller than or equal to 95. The lithium metal battery provided by the invention has excellent electrochemical performance, especially excellent capacity retention performance and expansion inhibition performance under a high-rate cycle condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of energy storage technology, and in particular to a lithium metal battery and an electronic device. Background Art

[0002] In recent years, as electronic products play an increasingly important role in our daily lives, people's requirements for the performance of lithium batteries have also continued to increase. At present, the theoretical capacity of graphite anode materials used in large-scale commercialization is limited, which is difficult to meet the demand for high energy density lithium batteries.

[0003] Lithium metal has a low standard electrode potential and a large theoretical gram capacity. Its metal element and alloy as negative electrode active materials can achieve a high operating voltage and energy density. However, during the charging process of lithium metal batteries, lithium ions are deposited unevenly on the surface of lithium metal, which easily forms lithium dendrite structures. Lithium dendrite structures not only reduce the deposition density of lithium ions, but can even pierce the diaphragm and cause a short circuit. They also aggravate the breakage and peeling of the SEI protective film on the negative electrode surface, causing it to lose its protective effect.

[0004] Therefore, it is urgent to provide solutions to inhibit the formation of lithium dendrites during the cycling of lithium metal batteries. Summary of the invention

[0005] The embodiments of the present application provide a lithium metal battery and an electronic device, which can inhibit the growth of lithium dendrites during the cycle process, thereby achieving better high-rate cycle performance of the battery while also improving volume expansion.

[0006] In a first aspect, an embodiment of the present application provides a lithium metal battery, comprising a negative electrode plate, a positive electrode plate, a separator and an electrolyte, wherein the negative electrode plate comprises a negative electrode collector and a lithium metal layer arranged on at least a portion of the surface of the negative electrode collector; the separator comprises a base film and a composite coating arranged on the surface of the base film facing the negative electrode plate, wherein the composite coating comprises a one-dimensional carbon material, and the degree of graphitization of the one-dimensional carbon material is X%, and 70≤X≤95.

[0007] Based on the lithium metal battery of the embodiment of the present application, the one-dimensional carbon material has excellent electrical conductivity and thermal conductivity. When it is coated on the side of the base film of the diaphragm facing the lithium metal negative electrode plate, the electric field, ion field and temperature field in the diaphragm-lithium metal electrode plate system can be uniformized, so that the deposition of lithium ions during the cycle is more uniform, thereby reducing the generation of lithium dendrites, slowing down the growth of lithium dendrites, and reducing the rupture of the SEI film, thereby improving the electrochemical performance of the lithium metal battery, especially the capacity retention rate and expansion rate of the cycle at a high rate; at the same time, the one-dimensional carbon material can embed a small amount of lithium, which can help improve the ion conduction rate during the lithium deposition process, promote the uniform deposition of lithium ions, inhibit the growth of lithium dendrites, and synergistically improve the capacity retention rate and expansion rate of the lithium metal battery at a high rate; on this basis, controlling the graphitization degree of the coated one-dimensional carbon material within the above range is beneficial to reducing the decomposition and film-forming reaction of the electrolyte on the composite coating, and improving the transmission rate of lithium ions and electrons on the surface of the composite coating, thereby further uniformizing the lithium ion deposition and improving the capacity retention rate and expansion rate of the lithium metal battery at a high rate.

[0008] In some embodiments, the electrolyte includes lithium bis(fluorosulfonyl)imide and lithium difluorooxalate borate. Based on the mass of the electrolyte, the mass proportion of lithium bis(fluorosulfonyl)imide is a%, 20≤a≤40, and the mass proportion of lithium difluorooxalate borate is b%, 0.1≤b≤2. Based on the above embodiments, the electrolyte of the lithium metal battery of the present application includes a specific content of lithium bis(fluorosulfonyl)imide and lithium difluorooxalate borate, which can inhibit the decomposition and film-forming reaction of the electrolyte on the composite coating, reduce the consumption of the electrolyte, and improve the transmission rate of lithium ions on the surface of the composite coating, thereby further uniformizing lithium deposition and improving the capacity retention rate and expansion rate of the lithium metal battery at a high rate cycle.

[0009] In some embodiments, the above-mentioned lithium metal battery satisfies 0.005≤b / (100-X)≤0.2. Based on the above-mentioned embodiments, the present application controls the relationship between the degree of graphitization of lithium difluorooxalatoborate in the electrolyte and the one-dimensional carbon material on the surface of the composite coating within the above-mentioned range, so that the content of lithium salt in the electrolyte is at a relatively balanced level, and the decomposition and film-forming reaction of the electrolyte on the composite coating can be better inhibited, and the consumption of the electrolyte can be reduced while increasing the transmission rate of lithium ions on the surface of the composite coating, thereby further uniformizing lithium deposition and improving the capacity retention rate and expansion rate of the lithium metal battery at a high rate cycle.

[0010] In some embodiments, based on the mass of the above-mentioned composite coating, the mass proportion of the above-mentioned one-dimensional carbon material is P%, 30≤P≤95. Based on the above-mentioned embodiments, the present application can further homogenize the electric field, ion field and temperature field in the diaphragm-lithium metal pole piece system by controlling the mass proportion of the one-dimensional carbon material in the composite coating on the surface of the base film within the above-mentioned range, so that the deposition of lithium ions during the cycle is more uniform, and the ion conduction rate during the lithium deposition process is synergistically improved, thereby reducing the generation of lithium dendrites, slowing down the growth of lithium dendrites, and reducing the rupture of the SEI film, thereby improving the capacity retention rate and expansion rate of lithium metal batteries cycled at high rates.

[0011] In some embodiments, the one-dimensional carbon material includes at least one of carbon nanofibers and carbon nanotubes. Based on the above embodiments, by selecting carbon nanofibers and carbon nanotubes as the one-dimensional carbon material in the composite coating on the surface of the base film of the present application, it has better electrical conductivity and thermal conductivity, and can better homogenize the electric field, ion field and temperature field in the diaphragm-lithium metal pole piece system, so that the deposition of lithium ions during the cycle is more uniform, thereby improving the capacity retention rate and expansion rate of the lithium metal battery at a high rate cycle.

[0012] In some embodiments, the thickness of the base film is Hμm, 5≤H≤20; and / or the thickness of the composite coating is hμm, 0.5≤h≤20. Based on the above embodiments, the present application can make the isolation film have relatively balanced performance by regulating the thickness of the base film and the thickness of the composite coating within the above range, and synergistically improve the capacity retention rate and expansion rate of the lithium metal battery at a high rate cycle.

[0013] In some embodiments, the peeling force between the base film and the composite coating is FN / m, 5≤F≤100. Based on the above embodiments, the peeling force between the base film and the composite coating of the present application is within the above range, indicating that the separator of the lithium metal battery of the present application has excellent mechanical properties, can maintain relative stability of the structure during the cycle, and synergistically improve the capacity retention rate and expansion rate of the lithium metal battery at a high rate cycle.

[0014] In some embodiments, the composite coating includes a binder, and the binder includes at least one of polyvinyl alcohol, polyacrylic acid, lithium polyacrylate, sodium polyacrylate, sodium carboxymethyl cellulose, sodium alginate, polyvinylidene fluoride, styrene-butadiene rubber or polymethyl methacrylate; based on the mass of the composite coating, the mass proportion of the binder is Q%, 5≤Q≤30. Based on the above embodiments, the composite coating of the present application further includes the above-mentioned content of the binder, which can improve the structural stability of the composite coating while taking into account the improvement of the conductive performance, thereby synergistically improving the capacity retention rate and expansion rate of the lithium metal battery at a high rate cycle.

[0015] In some embodiments, the composite coating includes nanoparticles, and the nanoparticles include at least one of gold, silver, silicon, tin, zinc or aluminum; based on the mass of the composite coating, the mass proportion of the nanoparticles is M%, 5≤M≤65. Based on the above embodiments, the nanoparticles have a certain affinity for lithium, and are dispersed in the three-dimensional network constructed by the one-dimensional carbon material in the composite coating. They can form a protective layer with the one-dimensional carbon material, which can reduce the longitudinal deposition of lithium metal, inhibit the growth of lithium dendrites, and further reduce the stress of lithium dendrites on the diaphragm, resist the puncture of lithium dendrites, and thus synergistically improve the capacity retention rate and expansion rate of lithium metal batteries cycled at high rates.

[0016] In a second aspect, an embodiment of the present application provides an electronic device comprising the above-mentioned lithium metal battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0018] Figure 1 This is a schematic diagram of the diaphragm structure of Example 2-1 of the present application.

[0019] Among them, 1-base film, 2-one-dimensional carbon material, 3-nanoparticles. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0021] A first aspect of an embodiment of the present application provides a lithium metal battery, including a negative electrode plate, a separator, an electrolyte and a positive electrode plate.

[0022] Negative electrode

[0023] The negative electrode plate includes a negative electrode current collector and a negative electrode material layer arranged on at least a portion of the surface of the negative electrode current collector, and the negative electrode material layer includes lithium metal.

[0024] The lithium metal includes at least one of elemental lithium or a lithium alloy, and the lithium alloy includes at least one of lithium tin, lithium zinc, lithium aluminum, lithium magnesium, lithium silver, lithium gold, lithium gallium, lithium indium, lithium platinum, lithium boron, lithium carbon or lithium silicon alloy.

[0025] In some of the embodiments, the negative electrode material layer may further include an amorphous carbon material, and the amorphous carbon may be soft carbon (low-temperature calcined carbon), hard carbon, mesophase pitch carbide or calcined coke, etc.

[0026] In some of the embodiments, the negative electrode material layer also includes a negative electrode binder. The present application does not particularly limit the type of negative electrode binder, as long as it is a material that is stable to the solvent used in the manufacture of the electrolyte or electrode. In some of the embodiments, the negative electrode binder includes a resin binder. Examples of resin binders include, but are not limited to, fluororesins, polyacrylonitrile (PAN), polyimide resins, acrylic resins, polyolefin resins, and the like. When an aqueous solvent is used to prepare the negative electrode mixture slurry, the negative electrode binder includes, but is not limited to, carboxymethyl cellulose (CMC) or its salt, styrene-butadiene rubber (SBR), polyacrylic acid (PAA) or its salt, polyvinyl alcohol, and the like.

[0027] In some embodiments, the negative electrode material layer further includes a conductive agent. The present application does not particularly limit the type of the negative electrode conductive agent, as long as the purpose of the present application can be achieved. For example, the negative electrode conductive agent can be at least one of acetylene black, Ketjen black, carbon nanotubes, carbon fibers, carbon dots or graphene, and the above-mentioned carbon nanotubes can include but are not limited to at least one of single-walled carbon nanotubes or multi-walled carbon nanotubes.

[0028] In some of the embodiments, the negative electrode may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, which may be at least one of the above-mentioned conductive agent and the above-mentioned binder. The present application has no particular restrictions on the mass ratio of the conductive agent and the binder in the conductive layer, and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the thickness of the conductive layer, as long as the purpose of the present application can be achieved, for example, the thickness of the conductive layer is 1μm to 10μm.

[0029] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the negative electrode current collector may include copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a polymer substrate covered with a conductive metal, etc. Among them, the conductive metal includes but is not limited to copper, nickel or titanium, and the material of the polymer substrate includes but is not limited to at least one of polyethylene, polypropylene, ethylene propylene copolymer, polyethylene terephthalate, polyethylene naphthalate or poly(p-phenylene terephthalamide). In the present application, there is no particular restriction on the thickness of the negative electrode current collector and the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4μm to 12μm, and the thickness of the single-sided negative electrode material layer is 30μm to 160μm. In the present application, the negative electrode mixture layer can be arranged on one surface in the thickness direction of the negative electrode current collector, or on two surfaces in the thickness direction of the negative electrode current collector. It should be noted that the "surface" here can be the entire area of ​​the negative electrode current collector or a partial area of ​​the negative electrode current collector. This application has no special restrictions as long as the purpose of this application can be achieved.

[0030] The present application has no particular restrictions on the compaction density of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the compaction density of the negative electrode sheet can be 1.0 g / cm 3 Up to 1.85g / cm 3 The present application has no particular limitation on the cold pressing pressure of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the cold pressing pressure of the negative electrode sheet can be 3 tons to 30 tons.

[0031] Diaphragm

[0032] In the present application, a diaphragm is usually provided between the positive electrode and the negative electrode. The diaphragm is used to separate the positive electrode plate and the negative electrode plate, reduce the problem of internal short circuit of the lithium metal battery, allow electrolyte ions to pass freely, and do not affect the electrochemical charge and discharge process.

[0033] In some of the embodiments, the diaphragm includes a base film and a composite coating disposed on the surface of the base film on the side facing the negative electrode plate, the composite coating includes a one-dimensional carbon material, and the graphitization degree of the one-dimensional carbon material is X%, 70≤X≤95. For example, the value of the graphitization degree of the one-dimensional carbon material can be 70, 73, 75, 76, 81, 83, 90, 91, 93, 95 or a value within the range composed of any two of these values. Coating the one-dimensional carbon material on the side of the base film of the diaphragm facing the lithium metal negative electrode plate can make the deposition of lithium ions more uniform, thereby reducing the generation of lithium dendrites, slowing down the growth of lithium dendrites, reducing the rupture of the SEI film, and thus improving the capacity retention rate and expansion rate of the lithium metal battery under high-rate cycling. On this basis, the graphitization degree of the one-dimensional carbon material is within the above range, which is conducive to further uniform lithium ion deposition and improving the capacity retention rate and expansion rate of the lithium metal battery under high-rate cycling.

[0034] In some of the embodiments, based on the mass of the composite coating, the mass proportion of the one-dimensional carbon material is P%, 30≤P≤95. For example, the mass proportion of the one-dimensional carbon material in the composite coating can be 30, 32, 34, 51, 60, 66, 80, 87, 90, 92, 95 or a value within the range formed by any two of these values. By controlling the mass proportion of the one-dimensional carbon material in the composite coating on the surface of the base film within the above range, the electric field, ion field and temperature field in the diaphragm-lithium metal electrode system can be further homogenized, thereby reducing the generation of lithium dendrites, slowing down the growth of lithium dendrites, reducing the rupture of the SEI film, and thereby improving the capacity retention rate and expansion rate of lithium metal batteries cycled at high rates.

[0035] In some embodiments, the one-dimensional carbon material includes at least one of carbon nanofibers and carbon nanotubes. Selecting carbon nanofibers and carbon nanotubes as the one-dimensional carbon material in the composite coating on the surface of the base film of the present application can make the deposition of lithium ions more uniform during the cycle process, and further improve the capacity retention rate and expansion rate of the lithium metal battery at a high rate cycle.

[0036] In some of the embodiments, the thickness of the base film is H μm, 5 ≤ H ≤ 20. For example, the thickness of the base film can be 5, 7, 9, 11, 12, 14, 15, 17, 19, 20 or a value within the range of any two of these values. The thickness of the composite coating is h μm, 0.5 ≤ h ≤ 20. For example, the thickness of the composite coating on the base film can be 0.5, 1, 3, 5, 6, 9, 10, 12, 15, 17, 19, 20 or a value within the range of any two of these values. By regulating the thickness of the base film and the thickness of the composite coating within the above range, the isolation membrane can have relatively balanced performance, and the capacity retention rate and expansion rate of the lithium metal battery cycled at a high rate can be synergistically improved.

[0037] In some embodiments, the peeling force of the base film and the composite coating is FN / m, 5≤F≤100. For example, the peeling force of the base film and the composite coating can be 5, 10, 13, 20, 26, 44, 62, 75, 88, 90, 100 or a value in the range formed by any two of these values. The peeling force between the base film and the composite coating is within the above range, indicating that the separator of the lithium metal battery of the present application has excellent mechanical properties, can maintain relative stability of the structure during the cycle, and synergistically improve the capacity retention rate and expansion rate of the lithium metal battery at a high rate cycle.

[0038] In some embodiments, the composite coating includes a binder, and the binder includes at least one of polyvinyl alcohol, polyacrylic acid, lithium polyacrylate, sodium polyacrylate, sodium carboxymethyl cellulose, sodium alginate, polyvinylidene fluoride, styrene-butadiene rubber or polymethyl methacrylate. Based on the mass of the composite coating, the mass proportion of the binder is Q%, 5≤Q≤30. For example, the mass proportion of the binder in the composite coating can be 5, 6, 12, 14, 21, 25, 29, 30 or a value within the range composed of any two of these values. The composite coating further includes the above-mentioned specific content of the binder, which can improve the structural stability of the composite coating while taking into account the improvement of the conductive performance, and synergistically improve the capacity retention rate and expansion rate of the lithium metal battery cycled at a high rate.

[0039] In some of the embodiments, the composite coating includes nanoparticles, and the nanoparticles contain at least one of gold, silver, silicon, tin, zinc or aluminum. Based on the mass of the composite coating, the mass proportion of the nanoparticles is M%, 5≤M≤65. For example, the mass proportion of the nanoparticles in the composite coating can be 5, 7, 10, 17, 20, 31, 38, 54, 64, 65 or a value within the range composed of any two of these values. The nanoparticles are preferably single particles. The nanoparticles are dispersed in the three-dimensional network constructed by the one-dimensional carbon material in the composite coating, which can reduce the longitudinal deposition of lithium metal, inhibit the growth of lithium dendrites, and resist the puncture of lithium dendrites, thereby synergistically improving the capacity retention rate and expansion rate of lithium metal batteries cycled at high rates.

[0040] In some of these embodiments, the basement membrane can be a nonwoven fabric or a composite membrane with a porous structure, and the material of the basement membrane can include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, polypropylene porous membrane, polyethylene porous membrane, polypropylene nonwoven fabric, polyethylene nonwoven fabric or polypropylene-polyethylene-polypropylene porous composite membrane can be used. The type of basement membrane can include at least one of woven membrane, nonwoven membrane, microporous membrane, composite membrane, rolled membrane or spun membrane.

[0041] In some of the embodiments, a surface treatment layer is provided on at least one surface of the substrate, and the surface treatment layer can be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. For example, the inorganic layer includes inorganic particles and a binder, and the present application has no particular restrictions on the above-mentioned inorganic particles, for example, it can include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the above-mentioned binder, for example, it can be at least one of the aforementioned binders. The polymer layer contains a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene).

[0042] The pore size of the diaphragm in the present application is 0.01 μm to 1 μm, and the thickness is 5 μm to 50 μm. In some embodiments, the thickness of the diaphragm is greater than 1 μm, greater than 5 μm, or greater than 8 μm. In some embodiments, the thickness of the diaphragm is less than 50 μm, less than 40 μm, or less than 30 μm. When the thickness of the diaphragm is within the above range, the insulation and mechanical strength can be ensured, and the rate characteristics and energy density of the lithium metal battery can be ensured.

[0043] Electrolyte

[0044] The electrolyte used in the lithium metal battery of the present application includes a lithium salt and a non-aqueous solvent that dissolves the lithium salt.

[0045] In some embodiments, the lithium salt includes lithium bis(fluorosulfonyl)imide and lithium difluorooxalate borate. Based on the mass of the electrolyte, the mass proportion of lithium bis(fluorosulfonyl)imide is a%, 20≤a≤40, and the mass proportion of lithium difluorooxalate borate is b%, 0.1≤b≤2. For example, the mass proportion of lithium bis(fluorosulfonyl)imide in the electrolyte may be 20, 24, 30, 33, 35, 37, 39, 40, or a value within the range of any two of these values. For example, the mass proportion of lithium difluorooxalate borate in the electrolyte may be 0.1, 0.2, 0.5, 0.6, 0.8, 1.0, 1.1, 1.4, 1.5, 1.8, 2.0, or a value within the range of any two of these values. The electrolyte includes a specific content of lithium bis(fluorosulfonyl)imide and lithium difluorooxalate borate, which can further uniformly deposit lithium and improve the capacity retention rate and expansion rate of lithium metal batteries cycled at high rates.

[0046] In some of the embodiments, the relationship between the degree of graphitization of the one-dimensional carbon material in the composite coating and the mass proportion of lithium difluorooxalate borate in the electrolyte satisfies 0.005≤b / (100-X)≤0.2. In some of the embodiments, 0.005≤b / (100-X)≤0.01. In some of the embodiments, 0.05≤b / (100-X)≤0.08. In some of the embodiments, 0.10≤b / (100-X)≤0.20. In some of the embodiments, 0.09≤b / (100-X)≤0.16. In some of the embodiments, 0.12≤b / (100-X)≤0.18. Controlling the relationship between the degree of graphitization of lithium difluorooxalate borate in the electrolyte and the one-dimensional carbon material on the surface of the composite coating within the above range can better inhibit the decomposition and film-forming reaction of the electrolyte on the composite coating, further uniform lithium deposition, and improve the capacity retention rate and expansion rate of lithium metal batteries cycled at high rates.

[0047] The present application has no particular restrictions on the types of the above-mentioned non-aqueous solvents, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents. The above-mentioned carbonate compounds may include but are not limited to at least one of chain carbonate compounds or cyclic carbonate compounds. The above-mentioned chain carbonate compounds may include but are not limited to at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate or methyl ethyl carbonate. The above-mentioned cyclic carbonate compounds may include but are not limited to at least one of ethylene carbonate, propylene carbonate, butylene carbonate or ethylene ethylene carbonate. The above-mentioned carboxylate compounds may include but are not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of ethylene glycol dimethyl ether, dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate.

[0048] positive electrode

[0049] The positive electrode includes a positive electrode collector and a positive electrode material layer disposed on at least one surface of the positive electrode collector.

[0050] The positive electrode material layer includes a lithium-containing transition metal composite oxide, and the lithium-containing transition metal composite oxide includes Lix Na z Co 1-y M y O2, wherein 0.6<x<0.95, 0≤y<0.15, 0<z≤0.03, M is at least one selected from the group consisting of Al, Mg, Ti, Mn, Fe, Ni, Zn, Cu, Nb, Cr and Zr. For example, the above subscripts may be 0.6<x<0.7, 0≤y<0.10, and 0<z<0.01; 0.7<x<0.8, 0.05<y<0.10, and 0<z<0.02; 0.8<x<0.9, 0.06<y<0.09, and 0<z≤0.03; 0.9<x<0.95, 0.07<y<0.08, and 0.01<z<0.02; 0.6<x<0.9, 0.08<y<0.15, and 0.01<z≤0.03. By adding the above-mentioned lithium-containing transition metal composite oxide to the positive electrode material layer in the lithium metal battery, and controlling the content ratio of each metal atom in the lithium-containing transition metal composite oxide, especially the content ratio of sodium atoms to meet the above-mentioned range, it is possible to improve both the high-temperature storage performance and the low-temperature discharge performance of the lithium metal battery.

[0051] In some embodiments, the positive electrode material layer includes a positive electrode conductive material. There is no limitation on the type of positive electrode conductive material, and any known conductive material can be used. Examples of positive electrode conductive materials may include, but are not limited to, carbon black such as acetylene black and Super-P; amorphous carbon such as needle coke; carbon nanotubes; graphene, etc. The above positive electrode conductive materials may be used alone or in any combination.

[0052] In some embodiments, the positive electrode material layer includes a positive electrode binder. The type of the positive electrode binder is not particularly limited, and in the case of a coating method, any material that can be dissolved or dispersed in a liquid medium used in electrode manufacturing can be used. Examples of positive electrode binders may include, but are not limited to, one or more of the following: resin polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, nitrocellulose, etc.; rubber polymers such as styrene-butadiene rubber, nitrile rubber, fluororubber, isoprene rubber, polybutadiene rubber, ethylene-propylene rubber, etc.; thermoplastic elastomer polymers such as styrene-butadiene-styrene block copolymer or its hydride, ethylene-propylene-diene terpolymer, styrene-ethylene-butadiene-ethylene copolymer, styrene-isoprene-styrene block copolymer or its hydride; soft resin polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymer, propylene-α-olefin copolymer; fluorine polymers such as polyvinylidene fluoride, polytetrafluoroethylene, fluorinated polyvinylidene fluoride, polytetrafluoroethylene-ethylene copolymer; polymer compositions having ion conductivity of alkali metal ions, etc. The above positive electrode binders may be used alone or in any combination.

[0053] There is no restriction on the type of solvent used to form the positive electrode slurry, as long as it is a solvent that can dissolve or disperse the positive electrode active material, the conductive material, the positive electrode binder and the thickener used as needed. Examples of solvents used to form positive electrode slurries may include any of aqueous solvents and organic solvents. Examples of aqueous media may include, but are not limited to, mixed media of alcohol and water or water, etc. Examples of organic media may include, but are not limited to, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran; amides such as N-methylpyrrolidone, dimethylformamide, and dimethylacetamide; non-protonic polar solvents such as hexamethylphosphoramide and dimethyl sulfoxide, etc.

[0054] Thickeners are usually used to adjust the viscosity of the slurry. In the case of using an aqueous medium, a thickener and a styrene-butadiene rubber emulsion can be used to slurry. The type of thickener is not particularly limited, and examples thereof may include, but are not limited to, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof. The above thickeners may be used alone or in any combination.

[0055] There is no particular limitation on the type of positive electrode current collector, which can be any known material suitable for use as a positive electrode current collector. Examples of positive electrode current collectors may include, but are not limited to, metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and materials such as carbon cloth and carbon paper. In some embodiments, the positive electrode current collector is a metal material. In some embodiments, the positive electrode current collector is aluminum.

[0056] In order to reduce the electronic contact resistance between the positive electrode current collector and the positive electrode material layer, the surface of the positive electrode current collector may include a conductive additive or a conductive coating. Examples of conductive additives may include, but are not limited to, carbon and precious metals such as gold, platinum, and silver. Examples of conductive coatings may include a mixture layer containing an inorganic oxide, a conductive agent, and a binder.

[0057] The present application also provides an electronic device, which includes the lithium metal battery of the present application. The electronic device includes but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor.

[0058] Example

[0059] Below, taking lithium metal batteries as an example, examples and comparative examples are given to more specifically illustrate the implementation of the lithium metal battery of the present application. Those skilled in the art will understand that the preparation method described in this application is only an example, and any other suitable preparation method is within the scope of this application. Various tests and evaluations are carried out according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0060] Example 1-1

[0061] 1. Preparation of positive electrode

[0062] The positive electrode active material NCM 811, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 96:2:2, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 75%, and stirred under the action of a vacuum mixer until the system becomes a uniform positive electrode slurry. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm and dried at 90°C; then, the above steps are repeated on the other surface of the positive electrode sheet to obtain a positive electrode sheet with a double-sided coating of positive electrode active materials. After the coating is completed, the positive electrode sheet is cold pressed, striped, and cut to obtain a 38mm×58mm positive electrode sheet for standby use.

[0063] 2. Preparation of negative electrode

[0064] A 20μm thick lithium metal foil is placed on one surface of a 8μm thick negative electrode current collector copper foil, and the metal lithium and the current collector are bonded by a roller to obtain a single-sided lithium foil negative electrode sheet; the above steps are repeated on the other surface of the negative electrode sheet to obtain a double-sided lithium foil negative electrode sheet. After striping and cutting, a 40mm×60mm specification negative electrode sheet is obtained for use.

[0065] 3. Preparation of electrolyte

[0066] In a dry argon atmosphere glove box, ethylene glycol dimethyl ether and 1,2-difluorobenzene were mixed in a mass ratio of 1:2 as a base solvent, and then lithium bis(fluorosulfonyl)imide and lithium difluorooxalate borate were dissolved in the base solvent to obtain an electrolyte. The mass proportions of lithium bis(fluorosulfonyl)imide and lithium difluorooxalate borate based on the total mass of the electrolyte are shown in Table 1, and the remainder is the base solvent.

[0067] 4. Preparation of diaphragm

[0068] (1) A porous polyethylene film with a thickness of 9 μm and a porosity of 51% is used as the base film;

[0069] (2) adding one-dimensional carbon material, nanoparticles and binder polyvinyl alcohol (weight average molecular weight 150,000) into a stirrer according to mass ratio, adding deionized water, and stirring evenly to form a composite coating slurry with a solid content of 5wt%;

[0070] (3) The slurry is uniformly coated on one surface of the base film and dried to obtain a separator.

[0071] 5. Preparation of lithium metal batteries

[0072] The positive electrode sheet and the negative electrode sheet prepared as above are connected to the pole lugs respectively. They are stacked via a diaphragm to obtain a laminated body. The composite coating of the diaphragm faces the negative electrode sheet. Then, the laminated body is stored in an aluminum laminated housing together with the electrolyte. The opening of the housing is heat-sealed, and a lithium metal battery is manufactured through steps such as formation and degassing.

[0073] 6. Test methods

[0074] (1) Graphitization degree test of one-dimensional carbon materials

[0075] High-purity silicon powder was used as the standard sample, and the 002 peak of the one-dimensional carbon material of the composite coating and the 111 peak of silicon were obtained by XRD testing. By comparing the 2θ angle of the 002 peak after calibration with the silicon standard sample, the Bragg formula was calculated to obtain the 002 peak crystal plane spacing d002 of the one-dimensional carbon material.

[0076] The graphitization degree of one-dimensional carbon material is X%=(0.344-d002) / (0.344-0.3354).

[0077] (2) Diaphragm thickness test

[0078] SEM test: The SEM characterization was recorded by a Philips XL-30 field emission scanning electron microscope at 10 kV and 10 mA.

[0079] (3) Composite coating and base film peeling force test

[0080] Cut the diaphragm into strips of 50 mm × 15 mm, attach the special tape for peeling force test to one side of the composite coating, and use the 180° peeling strength test method to test the peeling force between the composite coating and the base film. Test at least 5 parallel samples and calculate their arithmetic mean.

[0081] (4) Test on the mass ratio of nanoparticles in composite coating

[0082] The composite coating powder is collected by scraping on the surface of the diaphragm and its mass is weighed and recorded as M0. The composite coating powder with a mass of M0 is redispersed in water or N-methylpyrrolidone, washed and centrifuged several times to obtain a composite of nanoparticles and one-dimensional carbon materials, which is weighed and recorded as m0. The composite of nanoparticles and one-dimensional carbon materials with a mass of m0 collected above is placed in aqua regia solution for digestion, and the element content of nanoparticles in the digestion solution is determined by inductively coupled plasma (ICP) to obtain the mass m1 of the nanoparticles, and the mass proportion of the composite coating nanoparticles can be calculated as M% = 100% × m1 / M0.

[0083] (5) Test on mass proportion of one-dimensional carbon material in composite coating

[0084] The mass proportion of the one-dimensional carbon material in the composite coating can be calculated from M0, m0 and m1 measured in the above step (4) to obtain P%=100%×(m0-m1) / M0.

[0085] (6) High-rate cycle capacity retention and expansion rate test

[0086] Take a lithium metal battery, place it in a 25±5℃, normal pressure environment, charge it to 4.3V at a constant current of 1C, then charge it to 0.05C at the 4.3V constant voltage, let it stand for 5 minutes, discharge it to 2.8V at a constant current of 1C, let it stand for 5 minutes, this is a charge and discharge cycle process. Record the first cycle discharge capacity C0 and initial thickness T0. Perform 100 cycles of charge and discharge tests in the above manner, and record the 100th cycle discharge capacity C1 and the thickness after the cycle T1.

[0087] High rate cycle capacity retention rate % = C1 / C0×100%.

[0088] Cycle thickness expansion rate % = (T1-T0) / T0×100%.

[0089] The lithium metal batteries of the following embodiments and comparative example 1 differ from those of embodiment 1-1 only in that one-dimensional carbon materials of different types and different degrees of graphitization are selected according to the parameters shown in Table 1, and the mass proportion of the one-dimensional carbon material in the composite coating, the mass proportion of the nanoparticles, and the mass proportion of lithium bis(fluorosulfonyl)imide and lithium difluorooxalatoborate in the electrolyte are adjusted. The only difference between comparative example 2 and embodiment 1-1 is that the carbon material in the composite coating is carbon nanoparticles.

[0090] The performance test results of the lithium metal batteries of the embodiments and comparative examples are shown in Table 1 below.

[0091] Table 1

[0092]

[0093]

[0094] *In the above table, the calculation result of b / (100-X) is rounded to 3 decimal places; the P value of Comparative Example 2 is the mass percentage of carbon nanoparticles in the composite coating.

[0095] As can be seen from Table 1, the lithium metal batteries prepared in the embodiments of the present application have significantly improved high-rate cycle capacity retention rates and significantly reduced cycle thickness expansion rates, relative to Comparative Example 1 with a lower degree of graphitization; relative to Comparative Example 2 using non-one-dimensional carbon material carbon nanoparticles, the high-rate cycle capacity retention performance of the lithium metal batteries in each embodiment is significantly improved, and the cycle thickness expansion rate is significantly reduced.

[0096] In particular, the lithium metal battery prepared in the embodiment of the present application, when the mass proportion a% of lithium bis(fluorosulfonyl)imide in the electrolyte satisfies 20≤a≤40, and the mass proportion b% of lithium difluorooxalate borate satisfies 0.1≤b≤2, the lithium metal battery has a better high-rate cycle capacity retention rate and a lower cycle thickness expansion rate. In particular, the lithium metal battery prepared in the embodiment of the present application, when the relationship between the mass proportion of lithium difluorooxalate borate in the electrolyte and the degree of graphitization of the one-dimensional carbon material satisfies 0.005≤b / (100-X)≤0.2, the lithium metal battery has a better high-rate cycle capacity retention rate and a lower cycle thickness expansion rate. In particular, the lithium metal battery prepared in the embodiment of the present application, when the mass proportion P% of the one-dimensional carbon material satisfies 30≤P≤95, the lithium metal battery has a better high-rate cycle capacity retention rate and a lower cycle thickness expansion rate. In particular, the lithium metal battery prepared in the embodiment of the present application, when the one-dimensional carbon material includes carbon nanofibers and carbon nanotubes, the lithium metal battery has a better high-rate cycle capacity retention rate and a lower cycle thickness expansion rate. In particular, the lithium metal battery prepared in the embodiment of the present application, when the mass proportion Q% of the binder in the composite coating satisfies 5≤Q≤30, the lithium metal battery has a better high-rate cycle capacity retention rate and a lower cycle thickness expansion rate. In particular, the lithium metal battery prepared in the embodiment of the present application, when the composite coating includes the above-mentioned nanoparticles and the mass proportion M% satisfies 5≤M≤65, the lithium metal battery has a better high-rate cycle capacity retention rate and a lower cycle thickness expansion rate.

[0097] The lithium metal batteries of the following Examples 2-1 to 2-16 differ from those of Examples 1-18 only in that the thickness of the base film in the separator, the thickness of the composite coating, the type and mass ratio of the binder, and the type and mass ratio of the nanoparticles are adjusted according to Table 2. The lithium metal batteries of Examples 2-17 to 2-19 differ from those of Examples 1-18 only in that the mass ratios of the one-dimensional carbon material, the binder, and the nanoparticles are adjusted according to Table 2.

[0098] Table 2

[0099]

[0100]

[0101] It can be seen from Table 2 that the lithium metal battery prepared in the embodiment of the present application has a better high-rate cycle capacity retention rate and a lower cycle thickness expansion rate when the thickness Hμm of the base film is adjusted to satisfy 5≤H≤20, or the thickness hμm of the composite coating satisfies 0.5≤h≤20. When the composite coating includes the above-mentioned binder, and the mass proportion Q% of the binder in the composite coating satisfies 5≤Q≤30, the lithium metal battery has a better high-rate cycle capacity retention rate and a lower cycle thickness expansion rate. When the composite coating includes the above-mentioned nanoparticles, and the mass proportion M% of the nanoparticles in the composite coating satisfies 5≤M≤65, the lithium metal battery has a better high-rate cycle capacity retention rate and a lower cycle thickness expansion rate.

[0102] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A lithium metal battery, characterized in that: It includes a negative electrode plate, a positive electrode plate, a separator and an electrolyte, wherein the negative electrode plate includes a negative electrode current collector and a lithium metal layer arranged on at least a part of the surface of the negative electrode current collector; The diaphragm comprises a base film and a composite coating arranged on the surface of the base film facing the negative electrode plate, the composite coating comprises a one-dimensional carbon material, and the graphitization degree of the one-dimensional carbon material is X%, 70≤X≤95.

2. The lithium metal battery according to claim 1, characterized in that The electrolyte includes lithium bis(fluorosulfonyl)imide and lithium difluorooxalatoborate; Based on the mass of the electrolyte, the mass proportion of lithium bis(fluorosulfonyl)imide is a%, 20≤a≤40, and the mass proportion of lithium difluorooxalatoborate is b%, 0.1≤b≤2.

3. The lithium metal battery according to claim 2, characterized in that The lithium metal battery satisfies 0.005≤b / (100-X)≤0.

2.

4. The lithium metal battery according to any one of claims 1 to 3, characterized in that Based on the mass of the composite coating, the mass proportion of the one-dimensional carbon material is P%, and 30≤P≤95.

5. The lithium metal battery according to claim 4, characterized in that The one-dimensional carbon material includes at least one of carbon nanofibers and carbon nanotubes.

6. The lithium metal battery according to any one of claims 1 to 3, characterized in that The thickness of the base film is H μm, 5≤H≤20; and / or, The thickness of the composite coating is h μm, 0.5≤h≤20.

7. The lithium metal battery according to claim 6, characterized in that The peeling force of the base film and the composite coating is FN / m, 5≤F≤100.

8. The lithium metal battery according to any one of claims 1 to 3, characterized in that The composite coating includes a binder, and the binder includes at least one of polyvinyl alcohol, polyacrylic acid, lithium polyacrylate, sodium polyacrylate, sodium carboxymethyl cellulose, sodium alginate, polyvinylidene fluoride, styrene-butadiene rubber or polymethyl methacrylate; Based on the mass of the composite coating, the mass proportion of the binder is Q%, 5≤Q≤30.

9. The lithium metal battery according to any one of claims 1 to 3, characterized in that The composite coating includes nanoparticles, and the nanoparticles include at least one of gold, silver, silicon, tin, zinc or aluminum; Based on the mass of the composite coating, the mass proportion of the nanoparticles is M%, 5≤M≤65.

10. An electronic device, characterized in that: A lithium metal battery comprising the lithium metal battery according to any one of claims 1 to 9.